Phytochemical evaluation and antidiabetic potential (In silico) of corn silk (Zea mays L.) and jasmine (Jasminum sambac) - Bohari Bohari; Rimbawan Rimbawan; Zuraidah Nasution; Ekowati Handharyani (AcTion: Aceh Nutrition Journal, 2025)
Diabetes mellitus is a significant global health challenge, necessitating the exploration of novel therapeutics from natural sources for its treatment. This study aimed to identify the bioactive compounds in a combinatorial methanolic extract of corn silk (Zea mays L.) and jasmine flowers (Jasminum sambac) and predict their antidiabetic potential. The extract was analyzed using Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS). The identified compounds were evaluated in silico via molecular docking simulations against key antidiabetic protein targets: Glucagon-Like Peptide 1 (GLP-1), Insulin-like Growth Factor 1 (IGF-1), Glucose Transporter 4 (GLUT4), alpha-glucosidase, and superoxide dismutase (SOD). The analysis focused on the binding energy (ΔG). A total of 44 metabolites were identified in this study. Molecular docking results indicated that rothindin exhibited the highest binding affinity for GLUT4, with a binding energy of -9.9 kcal/mol. Rothindin and Chlorogenic Acid also showed significant potential as modulators of GLUT4 and α-glucosidase, respectively. In conclusion, the combined extract contains bioactive compounds, particularly roxindin and chlorogenic acid, which demonstrate significant in silico potential as antidiabetic agents.